2021
DOI: 10.26418/jppk.v10i1.44303
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penerapan Model Pembelajaran Crossword Puzzle Pada Pembelajaran Geografi Terhadap Hasil Belajar Siswa

Abstract: This study aimed to determine whether there are differences in student learning outcomes in the class applying expository learning models and classes that apply crossword puzzle learning models in geography learning for class XI IPS students of SMA Negeri 2 Sungai Raya. The research method used is quantitative experiments. The source of research data was primary data from the learning outcomes of students of class XI IPS of SMA Negeri 2 Sungai Raya on geography learning. The results showed that the average stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…Meanwhile, supported by previous research, the results of research conducted by Kurniati (2020) from Faculty of Teacher Training and Education of Universitas Tanjungpura. The result of this study shows an influence of students' learning outcomes who apply the GIS application in the learning process, where the effect is quite significant, namely 78.6 for those who apply the application and 67.6 for those who do not apply the application.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Meanwhile, supported by previous research, the results of research conducted by Kurniati (2020) from Faculty of Teacher Training and Education of Universitas Tanjungpura. The result of this study shows an influence of students' learning outcomes who apply the GIS application in the learning process, where the effect is quite significant, namely 78.6 for those who apply the application and 67.6 for those who do not apply the application.…”
Section: Introductionsupporting
confidence: 74%
“…Meanwhile, the researcher found that students' learning outcomes have improved but not drastically. It is supported by Nia Kurniati (2020) from Universitas Tanjungpura titled The Influence of GIS Media Use with QGIS on Geography Learning on Student Learning Outcomes of Class X Senior High School 6 Pontianak. She stated that QGIS affects improving student learning outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Barriers to learning in rotational symmetry material are the lack of readiness of the teacher in the learning process, limited delivery of material, and the teacher does not provide practice questions (Nurvita dkk., 2022). Proof of rotational symmetry in flat shapes can use origami media (Lubis & Tampubolon, 2014). Geogebra helps visualize and discover the concept of rotation in geometry (Hanafi dkk., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Folding symmetry and rotational symmetry geometry materials are still difficult material for students (Nurvita dkk., 2022). Students find it difficult to determine rotational symmetry in flat shapes (Lubis & Tampubolon, 2014). There is a gap between theory and reality, which makes this research important to do.…”
Section: Introductionmentioning
confidence: 99%
“…Open Access: https://ejournal.unma.ac.id/index.php/educatio membuat RPP, mengukur tujuan belajar siswa, dan mengevaluasi proses pembelajaran (Lestari et al, 2021). Guru perlu membangun kelas yang menarik dengan memilih dan menggunakan berbagai strategi pengajaran yang efektif (Muhtar, 2021).…”
unclassified